A Comparison of Design and Support Priorities of Nationally Appropriate Mitigation Actions. (June 2015) - Fridahl, Mathias; Hagemann, Markus; Röser, Frauke; Amars, Latif
In context of the 1992 UN Framework Convention on Climate Change, developing countries are asked to contribute to greenhouse gas control objectives by proposing so-called Nationally Appropriate Mitigation Actions (NAMAs). Although the concept provides developing countries with complete flexibility to design NAMAs, a majority of proposals seek international support. This article improves our understanding of the matching of NAMA design and international support by exploring (mis-) alignment between support providers' and NAMA developers' prioritization for NAMAs. The article assesses survey responses from support providers in light of records of NAMAs. We conclude that there is a mismatch between support providers' primary emphasis on systems for measuring emissions reductions and the lack of such provisions in existing NAMA proposals. Furthermore, sector preferences may create structural biases in NAMA support.